Beyond antibacterials – exploring bacteriophages as antivirulence agents. (April 2021) - Shen, Yang; Loessner, Martin J
Graphical abstract: Highlights: Surface receptor-mediated phage resistance often comes at a cost for fitness. Possible trade-offs may include attenuated virulence, and increased sensitivity to antibiotics and natural host defenses. Phage-derived products hold potential as antivirulence drugs that target bacterial virulence instead of direct killing. Abstract : Life-threatening infections caused by multidrug-resistant bacteria are becoming increasingly difficult to treat. There is growing interest in exploiting bacteriophages (or phages) to combat bacterial infections. Phages often target bacterial surface structures that may also be important for virulence. Upon phage challenge, these molecules may be lost or modified, resulting in phage resistance and possibly phenotypical conversion. Importantly, possible trade-offs may include lower fitness, increased sensitivity to antibiotics and immune defense mechanisms, and virulence attenuation. Although evolution of phage-resistance may be difficult to prevent, the trade-off phenomenon carries potential for antibacterial therapy. Here we present some insights into the molecular principles and significance of this coincidental interplay between phages, bacteria, and immune cells, and discuss the prospect of developing phage-derived products as antivirulence agents.